Master elk and the mountain lion. - London, Jonathan, 1947-; McLoughlin, Wayne - illus (New York : Crown Publishers, Inc., 1995)
A young tule elk grows up to become the master of his herd and defends it from the attack of a mountain lion.
Keywords: Tule elk -- Fiction; Elk -- Fiction; Pumas -- Fiction